PENGARUH UKURAN PERUSAHAAN DAN RETURN ON EQUITY TERHADAP KEBIJAKAN DIVIDEN PADA EMITEN SEKTOR ENERGI YANG TERDAFTAR DI BEI TAHUN 2021-2024 - Sagsepa, Raditya Bima; Ambarwati, Putri (TECHNOBIZ : International Journal of Business, 2026)
This study aims to analyze the effect of company size and profitability on dividend policy in energy sector issuers listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The study population consisted of 91 energy sector companies, while the sample consisted of 28 companies obtained through a purposive sampling method with a total of 112 observations. The research data is secondary data obtained from the annual financial reports of each company. Data analysis techniques used include panel data regression, classical assumption tests, coefficient of determination (R²), F-test, and t-test. Based on the results of the Chow and Hausman tests, the most appropriate model for this study is the Fixed Effects Model (FEM). The results show that the company size variable (Firm Size) has a t-value of -0.182680 with a probability value of 0.0000 <0.05, however, because the t-value is smaller than the t-table (2.055529), it is concluded that company size does not have a significant effect on dividend policy. Meanwhile, the Return on Equity (ROE) variable has a calculated t-value of 2.166240 > t-table (2.055529) with a probability value of 0.0332 < 0.05, thus concluding that profitability has a positive and significant effect on dividend policy. Simultaneously, the F-test results show a calculated F-value of 4.282876 > F-table (2.059539) with a significance value of 0.00000 < 0.05, indicating that company size and profitability jointly have a significant effect on dividend policy. This study provides empirical evidence that profitability is the primary factor influencing dividend policy in energy sector companies in Indonesia, while company size has no significant effect. These results reinforce that a company's ability to generate profits is the primary basis for management in determining dividend distribution policy to shareholders